PENGEMBANGAN UMKM DESA BEJIJONG GUNA MENINGKATKAN PEREKONOMIAN PASCA PANDEMI COVID-19 MELALUI RE-BRANDING USAHA - Chairul Putri, Cintya; Sukma Garini, Lituhayu; Rafi Syafuddin, Muhammad; Puspaningtyas, Anggraeny (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2024)
The Covid-19 pandemic has left some impact, especially on the economic sector, namely on SME players. Moreover, SME in tourism areas. One of them is in Bejijong Village which is feeling the impact of the Covid-19 pandemic. The Covid-19 pandemic has caused the cessation of all tourism sectors and SME. That must restore so that the SME economy can improve. The method of implementing the service carried out by the PPK ORMAWA BEM FISIP University 17 August 1945 Surabaya team in the Branding Class, Literacy Corner program consisted of visits, data collection, interviews, mentoring, output creation, monitoring, and reporting to publication. Through the Branding Class service, some Bejijong Village SMEs understand better the importance of branding for their businesses, can take product photos and manage their social media business with the assistance provided, and issue NIB for SME with the Mojokerto Industry and Trade Office. The results of the Community Service Branding Class Literacy Corner for the PPK ORMAWA BEM FISIP University 17 August 1945 Surabaya activity are expected to be able to contribute to increasing the knowledge of Bejijong Village Human Resources. This service is intended to motivate, and increase the creativity of SME in branding their business and can improve the economy of the people of Bejijong Village, especially for SME.